VR4Good Demos and Presentation - Aguilar, Alex; Aung, Oliver; Danenkov, Leo; Lalli, Ricky; Lee, Jonathan; MacKay, Nick; Martinez, Ana Karen; Orlandea, Radu; Ramsay, Nicholas; Ritter, Lukas; Ryzhov, Vlad; Sandor, Ioana; et al. (Emerging Media BC Community of Practice Meeting, 2019)
Sandor
Keywords: Riecke; Riecke_2019; SIAR; SIAR 2019; VR demo; VR exhibition; bernhard-riecke; patrick-pennefather; talkWithoutPaper